A Comparative Study of Cardiovascular Tolerability with Slow Extended Dialysis Versus Continuous Haemodiafiltration in the Critical Patient - Birne, R (2016)
Background: In the haemodynamically unstable patient the method of treatment of acute renal failure is still largely controversial. The purpose of our study was to compare slow extended dialysis with continuous haemodiafiltration in the critical patient with indication for renal replacement therapy and haemodynamic instability. Patients and Methods: This is a cohort study comparing in 63 ventilated critical patients a 12 month period when only continuous haemodiafiltration was used (n=25) with an equal period of slow extended dialysis (n=38). Our primary objective was to evaluate the impact of the dialytic procedure on cardiovascular stability in those patients. As secondary aims we considered system coagulation/thrombosis and predictors of mortality. In the two groups we analysed the first session performed, the second session performed and the average of all the sessions performed in each patient. Results: In these patients, mortality in the intensive care unit was high (68% in the continuous haemodiafiltration group and 63% in the slow extended dialysis group). We did not find any association between the dialytic technique used and death; only the APACHE score was a predictor of death. Slow extended dialysis was a predictor of haemodynamic stability, a negative predictor of sessions that had to be interrupted for haemodynamic instability, and a predictor of achieving the volume removal initially sought. Slow extended dialysis was also associated with less coagulation of the system. Conclusions: Our data suggested that slow extended dialysis use was not inferior to continuous haemodiafiltration use in terms of cardiovascular tolerability.